Adequate anticoagulation and ECMO therapy in COVID-19 patients with severe pulmonary embolism. (September 2021) - Gaisendrees, Christopher; Walter, Sebastian G; Elderia, Ahmed; Vollmer, Mattias; Kaya, Süreyya; Djordjevic, Ilija; Eghbalzadeh, Kaveh; Sabashnikov, Anton; Kahlert, Heike Anelie; Deppe, Antje-Christin; Böll, Boris; Madershahian, Navid; et al.
SARS-CoV-2 (COVID-19) infections have been recently shown to be associated with a high rate of thromboembolic events due to pro-coagulative mechanisms that have not yet been fully understood. This paper reports on a 55-year-old female COVID-19 patient with severe ARDS and pulmonary embolism (PE) complicated by cardiogenic shock after 12 days of hospitalization under initial prophylactic anticoagulation with low molecular weight heparin (LMWH). An ultima-ratio va (veno-arterial) ECMO implantation and subsequent rapid upgrade to vvaECMO due to insufficient oxygenation was performed. The patient developed severe coagulopathy with intrapulmonary bleeding. The present report aims to highlight and discuss the pros and cons of various anticoagulation strategies in COVID-19 patients focusing on current scientific debates to address this frequently observed complication in the current situation worldwide.